Free vibration analysis of an electro-elastic GPLRC cylindrical shell surrounded by viscoelastic foundation using modified length-couple stress parameter. Issue 5 (4th July 2021) - Ghabussi, Aria; Ashrafi, Negin; Shavalipour, Aghil; Hosseinpour, Abolfazl; Habibi, Mostafa; Moayedi, Hossein; Babaei, Behzad; Safarpour, Hamed
Abstract: Due to the rapid development of process manufacturing, composite materials with graphene-reinforcement have obtained commercially notices in promoted engineering applications. For this regard, vibrational characteristics of a cylindrical nanoshell reinforced by graphene nanoplatelets (GPL) and coupled with piezoelectric actuator (PIAC) is investigated. Also, the nanostructure is embedded in a viscoelastic medium. The material properties of piece-wise graphene-reinforced composite (GPLRC) are assumed to be graded in the thickness direction of a cylindrical nanoshell and estimated through a nanomechanical model. For the first time in the current study is considering the effects of piezoelectric layer, viscoelastic foundation, GPLRC, and size-effects on the frequency responses of the GPLRC cylindrical nanoshell coupled with PIAC and by assuming perfect bonding between the core (GPLRC cylindrical shell) and the piezoelectric layer. The governing equations and boundary conditions have been developed using minimum potential energy and solved with the aid of the generalized differential quadrature method. In addition, because of piezoelectric layer, Maxwell's equation is derived. The results show that viscoelastic foundation, piezoelectric layer, GPL distribution pattern, length scale parameter and GPL weight function have important role in the frequency characteristics of the GPLRC cylindrical nanoshell coupled with PIAC and surrounded by viscoelastic foundation. The results of the current study are useful suggestions for design of materials science, micro-electro-mechanical systems, and nanoelectromechanical systems such as nanoactuators and nanosensors. Communicated by Francesco Tornabene.